Nonprofit participation in collective impact: A comparative case. Issue 4 (8th August 2017) - Cooper, Katherine R.
Abstract: Collective impact represents an increasingly common approach to cross-sector collaboration that relies upon coordinated efforts and shared measurement, yet questions remain as to the role of nonprofits in these partnerships. This case study explores nonprofit participation across two collective impact sites. Findings suggest that nonprofit leaders participate, but the conditions of collective impact partnerships impact their participation. Variations in collective impact conditions limit nonprofit participation as expressed through authority, data and financial resources, and discursive legitimacy.